THE PRODUCTION OF SOCIETY WITH LIMITED LIABILITY «IZOPLAST» FOR RAILWAYS. EXPERIENCE IN MANUFACTURING, ENGINEERING, CERTIFICATION. PROBLEMS AND TASKS - Zlakazov, O. B.; Ovodov, O. V.; Shupik, M. S. (Science and Transport Progress, 2006)
The problem questions of production and planning of polymeric insulators are described in the article.